2010
DOI: 10.1093/humrep/deq309
|View full text |Cite
|
Sign up to set email alerts
|

A novel embryo identification system by direct tagging of mouse embryos using silicon-based barcodes

Abstract: Our results demonstrate the feasibility of a direct embryo labeling system and constitute the starting point in the development of such systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 10 publications
2
30
0
Order By: Relevance
“…1). These barcodes have already been used by our group to tag mouse embryos by their microinjection into the perivitelline space (Novo et al, 2011).…”
Section: Barcode Design and Fabricationmentioning
confidence: 99%
See 2 more Smart Citations
“…1). These barcodes have already been used by our group to tag mouse embryos by their microinjection into the perivitelline space (Novo et al, 2011).…”
Section: Barcode Design and Fabricationmentioning
confidence: 99%
“…The fabrication process has been previously described (Fernández-Rosas et al, 2009;Novo et al, 2011).…”
Section: Barcode Design and Fabricationmentioning
confidence: 99%
See 1 more Smart Citation
“…1 In fact, fabrication of biological microelectromechanical systems for a wide range of applications, such as cell tracking, 2 embryo tagging 3 or drug delivery, [4][5][6] has been achieved. The application of biological microelectromechanical systems has acquired special importance due to their potential use in creating systems able to deliver a drug, in a controlled manner, to a specific target cell.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, a careful approach is required, because no studies with sufficiently long durations have been performed to ensure that there are no effects of electromagnetic waves [15][16][17][18][19]. Recent studies have investigated direct insertions into the zona pellucida and perivitelline space in each embryo using a barcode made of polysilicon with the goal of preventing mix-ups [20][21][22][23][24]. It has been reported that polysilicon barcode tagging can be used to identify individual mouse embryos.…”
Section: Discussionmentioning
confidence: 99%